An inter-temporal CGE model with fiscal and sector balances - Nana, Ganesh (School of Management Working Papers, 1995)
This paper records progress to date in the development of an inter-temporal version of the Research Project on Economic Planning’s Joanna CGE model. The standard version includes 22 industries, with relative price induced substitution between capital and labour in production and also between imported and domestic commodities in both production and consumption. It is solved for one period and model experiments can be specified to examine issues in a comparative static framework. In moving to a multi-period model the features introduced focus on forward-looking investment and consumer behaviour. In addition, explicit modelling of government and private sector income and expenditure is integrated into this cge framework. Assumptions relating to end-period investment and debt ratios are necessary in order to generate a steady-state solution. A twelve-industry model of the New Zealand economy is constructed with a database commencing from 1990 input-output relationships. The model is constructed and solved over a horizon of 20 periods using the Gempack suite of programs. Two comparative dynamic exercises are discussed, an external price shock and an internal demand shock. A comprehensive flow-of-funds analysis, however, awaits the inclusion of a monetary sector.